Journal of Midwifery and Women's Health Vol.57 No.1, January/February 2012 - Redaksi (Elsevier, 2012)
- Patient Education from the Jpurnal of Midwifery & Women's Health : Share with Women - Directive Versus Supportive Appoarches Used by Midwives When Providing Care During the Second Stage of Labor